Rural livelihoods in Mon State: Evidence from a representative household survey - Filipski, Mateusz J.; van Asselt, Joanna; Nischan, Ulrike; Belton, Ben; Htoo, Kyan; Win, Myat Thida; Hein, Aung; Kham, L. Seng; Naing, Zaw Min; Payongayong, Ellen; Boughton, Duncan (International Food Policy Research Institute, 2017)
The purpose of this report is to provide information and analysis to government, civil society, and donors interested in improving the well-being of the rural population of Mon State, Myanmar. Specifically, the report analyzes the different sources of income for rural households, as well as their socioeconomic characteristics, with a view to helping identify constraints on growth and potential pathways to improving incomes. The overall picture that emerges is one of a struggling agricultural sector and an economy heavily dependent on services for local employment and on international migration for income. The analysis is based on a sample of 1,632 rural households, designed to be representative of rural households in Mon State as a whole. The survey included a household questionnaire and a community survey, and gathered information on demographics, all economic aspects of the household, and access to infrastructure and services at the community level.